2004
DOI: 10.1007/s10211-004-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Meadow voles and prairie voles differ in the percentage of conspecific marks they over-mark

Abstract: Many terrestrial mammals scent mark in areas containing the scent marks of conspecifics, and thus, may deposit their own scent marks on top of those that were deposited previously by conspecifics. This phenomenon, known as over-marking appears to play a role in same-sex competition or mate attraction. The present study determines whether meadow and prairie voles avoid over-marking the scent marks of conspecifics, target the scent marks of conspecifics and over-mark them, or randomly over-mark the scent marks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…Scent marking took place in a T-shaped arena constructed of opaque green acrylic, which simulates an intersection of two vole runways (Ferkin et al 2004; Hobbs and Ferkin 2011a). Arms and stem of the arena measured 25 cm long × 13 cm wide × 15 cm high.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scent marking took place in a T-shaped arena constructed of opaque green acrylic, which simulates an intersection of two vole runways (Ferkin et al 2004; Hobbs and Ferkin 2011a). Arms and stem of the arena measured 25 cm long × 13 cm wide × 15 cm high.…”
Section: Methodsmentioning
confidence: 99%
“…In many species of small mammals, females compete for territories (Wolff 1993), and over-mark the scent marks of female conspecifics (Hurst 1990; Ferkin et al 2004). For example, female meadow voles, Microtus pennsylvanicus , scent mark within their territories (Brown and Macdonald 1985) and presumably over-mark the scent marks of female conspecifics to signal their residency in that area (Ferkin et al 2004; Ferkin and Pierce 2007). However, female voles occupy territories that vary in the quality and quantity of forage (Madison 1980; Batzli 1985; Bergeron and Jodoin 1989; Bergeron et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Third, in the study involving prairie voles, the identity of the top-and bottom-scent male donors was arbitrary. Given that female prairie voles form pair bonds with their mates (Carter and Getz 1993), it is likely that, if the mate was present in the territory, his marks would be more likely to be on top of those of male intruders (Ferkin et al 2004b). Fourth, Thomas (2002) examined the response of females to tethered male prairie voles, a situation that does not resemble the mating behavior of voles in free-living populations (Carter and Getz 1993;Getz and Carter 1996).…”
Section: Is It Better To Be On Top Than On the Bottom Of An Over-mark?mentioning
confidence: 97%
“…One possible tactic to limit rival male access to information on female reproductive state is for dominant males to overmark female scent marks (Lewis 2005). This male reproductive tactic is common in several species of vole (Ferkin et al 2004), has been shown to occur in ring-tailed lemurs (Kappeler 1998), and is suggested for owl monkeys (Wolovich and Evans 2007). In sifaka, males overmark female scent marks more frequently in the mating season and during intergroup encounters (Lewis 2005).…”
Section: Olfactory Cues To Female Receptive Statementioning
confidence: 99%